Pembinaan Kewirausahaan Produk Kerupuk Tahu di Desa Sukosari Kecamatan Tamanan Kabupaten Bondowoso - Rizal Perlambang CNAWP (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Tofu is a traditional food popular in Indonesia due to its delicious taste, affordability, and high nutritional content. However, tofu production in Indonesia is still dominated by simple technology, leading to low efficiency and less competitive selling prices. Product diversification efforts are needed to increase added value, such as processing raw tofu into tofu crackers. This Community Service activity aims to develop entrepreneurship among students of the Agribusiness Management Study Program at Jember State Polytechnic, particularly in the production of tofu crackers. The methods used include providing entrepreneurship materials, training in tofu cracker production, and conducting discussions and evaluations of the results. The activity outcomes indicated a shift in students' mindsets from job seekers to job creators, accompanied by high motivation for entrepreneurship. Students also learned tofu cracker production techniques, starting from material grinding, mixing, steaming, to frying, resulting in a nutritious, crispy product that meets consumer preferences. The feasibility analysis of the tofu cracker business showed profitable results, as seen from the indicators of BEP (unit), BEP (price), R/C Ratio, and ROI. This activity successfully enhanced students' skills, motivation, and knowledge while opening potential business opportunities for the surrounding community. It is hoped that the outcomes of this community service will benefit the community and MSME actors.